About simple philosophy of solving even simpler yet interesting geometry problems - Kašuba, Romualdas; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2019)
Geometry problems are important for training of the mind, imagination and other highly valuable human abilities, however, dealing with geometry tasks is remarkably diﬃcult even for the brightest students. There do not exist, as it seems, universal methods enabling one to solve all or even most of geometry problems. The authors share their life-long experience about some methods of approaching problems, which, when done properly, make some diﬃcult problems not so diﬃcult.